The association between pre‐diagnostic levels of psychological distress and adverse effects after radical prostatectomy - Rasmus Nilsson; Thomas Næss‐Andresen; Tor Åge Myklebust; Tomm Bernklev; Hege Kersten; Erik Skaaheim Haug (BJUI Compass)
Abstract Objectives To prospectively analyse the associations between pre‐diagnostic levels of anxiety and depression and patient‐reported urinary and sexual adverse effects after radical prostatectomy in a population‐based setting. Patients and Methods In three Norwegian county hospitals, men referred with a suspicion of prostate cancer were asked to fill out a patient‐reported outcome measurement (PROM) questionnaire prior to prostate biopsy. Those who later underwent radical prostatectomy were stratified into three distress groups according to their Hopkins Symptom Checklist 5‐score. Additional PROM questionnaires, including the EPIC‐26 to measure adverse effects, were collected at 6 and 12 months postoperatively. Multivariable mixed models were estimated and post hoc pairwise comparisons performed to explore differences in adverse effects between distress groups. Results A total of 416 men were included at baseline and of those, 365 (88%) returned questionnaires at 6 months and 360 (87%) at 12 months. After adjusting for confounders, men with high distress at baseline had worse urinary incontinence domain score (58.9 vs. 66.8, p = 0.028), more urinary bother (64.7 vs. 73.6, p = 0.04) and a higher risk of using incontinence pads (70.6% vs. 54.2%, p = 0.034) at 6 months than those with low distress. There was no difference in the sexual domain scores between distress groups postoperatively, but the high‐distress group expressed more sexual bother (24.9 vs. 37.5, p = 0.015) and the intermediate‐distress group had a greater probability of using sexual medications or devices (63.8% vs. 50.0%, p = 0.015) than the low‐distress group at 6 months. At 12 months scores generally improved slightly and differences between distress groups were less evident. Conclusion Men with higher levels of anxiety and depression before prostate biopsy report more urinary and sexual adverse effects after radical prostatectomy. This should be considered both in treatment decision‐making and during follow‐up after radical prostatectomy.